Malnutrition Decreases Antibody Secreting Cell Numbers Induced by an Oral Attenuated Human Rotavirus Vaccine in a Human Infant Fecal Microbiota Transplanted Gnotobiotic Pig Model - Michael, Husheem; Langel, Stephanie N.; Miyazaki, Ayako; Paim, Francine C.; Chepngeno, Juliet; Alhamo, Moyasar A.; Fischer, David D.; Srivastava, Vishal; Kathayat, Dipak; Deblais, Loic; Rajashekara, Gireesh; Saif, Linda J.; et al. (Frontiers in Immunology, 2020)
Human rotavirus (HRV) is a leading cause of morbidity and mortality in children, especially in developing countries. Malnutrition is prevalent in these countries, which may contribute to the decreased oral vaccine efficacy, posing a concern for global health. Neonatal gnotobiotic (Gn) pigs closely resemble human infants in their anatomy, physiology, and outbred status and are a unique model to investigate malnutrition, oral live attenuated HRV (AttHRV) vaccination, and subsequent virulent HRV (VirHRV) challenge. We evaluated the impact of malnutrition on AttHRV vaccine efficacy and B cell immune responses in neonatal germfree (GF) or Gn pigs transplanted with human infant fecal microbiota (HIFM). Pigs were fed either deficient or sufficient bovine milk diets. Malnutrition did not significantly affect the serum and intestinal contents total or HRV-specific IgG and IgA antibody titers pre VirHRV challenge. However, HRV-specific IgG and IgA antibody secreting cells (ASCs) were reduced in blood or intestinal tissues following AttHRV vaccination and pre VirHRV challenge in deficient HIFM transplanted pigs. Furthermore, post-VirHRV challenge, deficient HIFM pigs had decreased total Ig and HRV-specific IgG and IgA antibody titers in serum or intestinal contents, in addition to decreased HRV-specific IgG and IgA ASCs in blood and ileum, compared with sufficient HIFM pigs. Our results indicate that deficient diet impairs B cell mucosal and systemic immune responses following HRV vaccination and challenge. The impaired immune responses contributed to the decreased protective efficacy of the AttHRV vaccine, suggesting that malnutrition may significantly reduce the effectiveness of oral HRV vaccines in children in developing countries.